Case report: Initial presentation of pancreatic schwannoma as cystic pancreatic mass treated with classic Whipple’s procedure - Jemaneh, Zekewos Demissie; Zemedkun, Nahom; Nurlegn, Serkalem; Woldeamanuel, Amanuel Mamuye; Seife, Henok; Birhanu, Yohannes; Belachew, Bethelhem Berhanu (Frontiers in Gastroenterology, 2024)
Pancreatic schwannomas are exceedingly rare tumors arising from Schwann cells of the peripheral nerve sheath within the pancreas. Often asymptomatic or presenting with nonspecific symptoms, these tumors pose a diagnostic challenge due to their mimicry of other pancreatic neoplasms on imaging studies. Histologically, pancreatic schwannomas demonstrate spindle cell proliferation with a distinct Immunohistochemical profile, including positive staining for S-100 protein. Surgical resection remains the cornerstone of treatment, with excellent long-term prognosis following complete excision. Here, we present a case report of a pancreatic schwannoma in a woman presenting with a cystic pancreatic mass, underscoring the importance of considering this rare entity in the differential diagnosis of pancreatic lesions.